Optimization process of vaccine production of outer membrane vesicle from Neisseria meningitidis associated with Zika virus (Research, Society and Development, 2023)
Several vaccine prototypes were made using variations in concentration, volume, time and speed of agitation. From these prototypes, some characterization assays were carried out, such as the analysis of particle size and zeta potential, where it was possible to determine the size of the nanoparticles, the polydispersity index, with the most promising samples having a size of 252.1nm ± 71.2 nm. The polydispersity index was 0.572 ±0.02, the standard deviation being a little high due to the presence of free viral particles and some associated vesicles. It is noteworthy that the isolated vesicle has a size of 140 to 160nm and the polydispersity index of 0.513 demonstrates that we do not have interference in the sample of our vesicle (it is known that the size of the viral particle of Zika virus is between 40 and 60nm). Cytotoxicity testing was done to analyze whether they have cytotoxic profiles and also demonstrate that the prototype's neutralization and inactivation method works correctly. The analysis of the protein profile of some of the samples revealed that there are two major Zika virus proteins in the fused proteasome, namely the E protein, which is directly involved in the recognition of host cell receptors, and the C protein, which is related to capsid assembly, in addition to playing an important role in the immune response.